Long-term outcome following upper extremity replantation after major traumatic amputation. Issue 1 (December 2017) - Mattiassich, G.; Rittenschober, F.; Dorninger, L.; Rois, J.; Mittermayr, R.; Ortmaier, R.; Ponschab, M.; Katzensteiner, K.; Larcher, L.
Abstract Background Amputations in general and amputations of upper extremities, in particular, have a major impact on patients' lives. There are only a few long-term follow-up reports of patients after macro-replantation. We present our findings in contrast with the existing literature. Methods Sixteen patients with traumatic macro-amputation of an upper extremity were eligible for inclusion in this study. Altogether, the patients underwent replantation in 3 institutions between 1983 and 2011. Results Twelve male and four female patients with an average age at injury of 40.6 years (range, 14–61 years) were included in this study. The mean follow-up period was 13.5 years (range, 4.4–32.6 years; SD, 5.7 years). The mean disabilities of the arm, shoulder and hand (DASH) outcome measure was 41 (range, 5.2–94.8; SD, 18.2), functional independence measurement (FIM) was 125 (range, 120–126; SD, 1.8). Chen I representing very good function was accounted in six, Chen II representing good function in eight, Chen III (fair) in one and Chen IV (bad function) in one patient. Conclusions We found that while the majority of the included patients exhibited good or very good function of the extremity, none of the replanted appendages regained normal levels of functionality. In addition, all participants were very satisfied with their outcomes. Positive long-term results with high rates of subjective satisfaction are possible after replantation of upper extremities.